2011
DOI: 10.1007/978-3-642-23330-2_29
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Behavior in Collaborative Networks

Abstract: Abstract. Many factors such as weak partner commitment, lack of proper partners' alignment on interest and values, individualism, lack of flexibility, and loss of autonomy may cause partnership's failures in collaborative networks. Most of these serious causes for conflicts in collaborative networks are rooted in partner's behavior, therefore analyzing and modeling the behavioral aspects of collaborative networks are important to enforce their success. This paper first addresses two kinds of behavior related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some studies restrict e-government to Internet-enabled applications, with business processes do not use technology or focus on interactions between government and external groups; e.g. [38] describes a semantic platform for e-government; [39] presents a system for egovernment, and [40] proposes a collaborative network. They are classified as models in this study.…”
Section: ) Model Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies restrict e-government to Internet-enabled applications, with business processes do not use technology or focus on interactions between government and external groups; e.g. [38] describes a semantic platform for e-government; [39] presents a system for egovernment, and [40] proposes a collaborative network. They are classified as models in this study.…”
Section: ) Model Typesmentioning
confidence: 99%
“…1) Cost/economics drive: although e-government aims to improve efficiency, effectiveness, cost and transparency, no studies have been found within the list of selected articles that consider economic aspects. 1 (1,9%) Framework [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65] 24 (46,2%) Ontology -0 (0%) Metamodel [31] 1 (1,9%) Conceptual Model [66], [36], [35], [67], [34], [33], [32] [68], [69], [70], [71], [72], [73], [74], [75], [40], [76], [77], [39] , [38], [78], [37] [79], [80] 2) Value drive: four articles (7,7%) aimed at adding value on issues such as improving decision making and ...…”
Section: ) Model Focusmentioning
confidence: 99%
See 1 more Smart Citation